Raman spectroscopy of the photosensitive pigment Prussian blue. (17th April 2018) - Moretti, Giulia; Gervais, Claire
Abstract: Prussian blue is a pigment highly sensitive to electromagnetic radiation, visible light included. This photosensitivity, associated with a complex redox behavior, causes a vulnerability even to Raman lasers, with the possibility of sample alteration or irreversible damage. In this study, we systematically explored the influence of the laser wavelength and laser power on different types of Prussian blue pigments, soluble and insoluble. The use of different laser wavelengths does not influence the position of the characteristic peak, though it affects the signal‐to‐noise ratio. The latter can be improved by increasing the number of accumulations and/or the acquisition time. Furthermore, we evaluated a safe level of Raman laser excitation or "safe zone" with laser power between 0.005 and 0.06 mW, where Raman analysis can be performed without laser‐induced artifacts or damage for the sample. These artifacts may affect the characteristic spectral signature of the two different Prussian blue, leading to a wrong identification of the pigments. Moreover, artifacts can also hide features arisen from fading in objects presenting non‐visible alterations of Prussian blue. Abstract : Prussian blue is a highly photosensitive pigment and its integrity can be affected by Raman lasers. We thus evaluated a safe level of Raman laser excitation or "safe zone" (0.005 – 0.06 mW) where Raman analysis can be performed without laser‐induced artifacts or damage for the sample. These artifacts may affect characteristic spectral signatures of different Prussian blues. The use of different laser wavelengths does not influence the position of the characteristic peak, though it affects the signal‐to‐noise ratio.